ANALISIS KEPUASAN PELANGGAN SEKOLAH TERHADAP KINERJA PELAYANAN PERPUSTAKAAN SMPN 3 SENTOLO - Gati Sujatmi; Agustina Sri Purnami; Rejokirono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to analyze the level of school customer satisfaction on service performance and library management at SMPN 3 Sentolo. This type of research is a sequential explanatory method. The study population consisted of 576 students at SMPN 3 Sentolo using proportional sampling, resulting in a sample of 235 students. Data collection techniques: questionnaires, interviews, observation and documentation. The results of the research on the performance of the library service at SMPN 3 Sentolo are 81.04% in the satisfactory category. The four components are Collection Sub variable 80.81%, Infrastructure 80.94%, Library services 81.78%, Library reinforcement 80.52%. And includes performance management of library services from Planning to compiling work programs, Organizing to compiling organizational structures and division of tasks, Implementation of carrying out predetermined work program activities, Supervision, Evaluation of work program activities Customer satisfaction is obtained in very satisfying and satisfying categories determined by how management planning, organizing, implementation and supervision.